Teacher-made tests on Bahasa Indonesia subject for school examinations in public vocational high school of Bengkulu province - Gumono Gumono (JOALL (Journal of Applied Linguistics and Literature), 2022)
The purpose of this study was to identify and describe the use of operational verbs based on Anderson’s taxonomic cognitive domain on test items of Indonesian language exams in the public vocational high school in Bengkulu, Indonesia. This is qualitative in nature employing descriptive method as the research design. The data were obtained from test items of Indonesian language school examinations in a public senior vocational school which delivered to twelve graders in the academic year of 2019 with 45 questions in total. The data were documented and analyzed qualitatively. This turned out that operational verbs of the cognitive realm based on Anderson’s taxonomy are two items of remembering, two items of classifying, an item of summarizing, four items of inferring, an item of predicting, three items of interpreting, an item of executing, six items of analyzing, twenty items of selecting, two items of assessing, an item of checking, and two items of formulating which accounted for 24 verbs in total. However, the shows that only 12 verbs on the 12 test items are considered high-level thinking skills which resulted in suggestions to consider